Psychospołeczne czynniki ryzyka w środowisku pracy. Rekomendacje dla praktyki poradniczej - Piorunek, Magdalena; Werner , Iwona (Studia Edukacyjne, 2018)
The article presents the psychosocial hazards of the work environment resulting from the interaction between the content of work, organization and management of work processes, and its environmental determinants as well as competences and needs of those who provide work. Selected groups of psychosocial hazards were presented resulting, among others, from the task design, workpace and workload, decision latitude and control, culture and organizational function, interpersonal relations in the workplace, the specifics of career progression, and the home-work interface. The context of the proposed considerations is the phenomenon of work-related stress, thus selected work-related stress models were presented. It is quite well established that stress can contribute to the deterioration of the psychosocial, physiological and health functioning of employees. Finally, recommendations for education and counseling were presented, the effect of which could be to counteract the negative effects of psychosocial risks at work.